PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN PRODUK TUPPERWARE (Studi pada Konsumen PT. Tiara Kinarya Sakti, Kudus) - Yanuarista, Tiara; Waluyo, Handoyo Djoko; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Tupperware is a pioneer of products made from plastics that offer safety for health and the environment. However, the advantages offered by Tupperware felt not optimal. Many complaints by consumers to the company, among others, the long warranty service, product names are difficult to remember, limited product availability, and so forth. So that these things will obviously affect customer satisfaction.The purpose of this study was to determine the effect of brand image, product quality, and customer value to customer satisfaction in using Tupperware products. This type of research is explanatory research. The population in this research that consumers PT. Tiara Kinarya Sakti and the number of samples taken was 100 respondents. The sampling technique in this study using purposive sampling. The analytical method used is cross tabulation, correlation, determination, simple linear regression, multiple, t test and F test with SPSS version 16.Based on the survey results revealed that the brand image, product quality, and customer value provides a positive and significant influence on customer satisfaction, either partially or simultaneously. X variables that have the most influence on customer satisfaction is customer value.Some recommends that could give the author is to intensify promotion of Tupperware products, to check the goods before the customer leaves the distributor’s office, adding stock warrany Tupperware products, giving an adward or reward to loyal customers, improve hospitality and speed in serving customers, and more spread sales force with the lure of an extra bonus if successfully exceeded the target.